Modulations of Digestive and Metabolic Enzymes Profiles during Restriction Feeding in Rohu Labeo rohita Fingerlings. (15th March 2021) - Dar, Showkat Ahamd; Srivastava, Prem Prakash; Nazir, Mir Ishfaq; Jahan, Iffat; Varghese, Tincy; Hajam, Irshad Ahmad; Gupta, Subodh
Abstract: A 60‐d experimental trial was conducted to evaluate the effects of alternative feeding, restriction feeding, and refeeding on digestive enzymes, metabolic enzymes, and metabolites in Rohu Labeo rohita fingerlings. Fish weighing around 13 ± 2 g were randomly distributed into four treatment groups and a control group. The control group was fed with 3% body mass twice a day throughout the experiment. The four treatment groups consisted of T1 (alternate day feeding), T2 (0.5% feeding), T3 (1% feeding), and T4 (2% feeding). The fish were fed for the first 30 d according to the feeding schedule, and from day 31 onwards all of the treatment groups were fed the same rations as were the control fish up to 60 d. The samples were collected on days 0, 15, 30, 45, and 60 of the experimental trial. The activity of digestive enzymes decreased significantly ( P < 0.05) in T1, T2, and T3 with respect to the control, and the lowest activities were found on day 30 of the experiment. The glucose‐6‐phospahate dehydrogenase activity decreased with the level of restriction feeding, with the lowest activity occurring at day 30 in the T2 group, and it improved with refeeding. The serum glucose, triglycerides, and cholesterol concentrations decreased, with the lowest levels occurring in the T2 group at day 30. The current study revealed that restriction feeding and refeeding affected the digestion and metabolism of Rohu fingerlings within a short period of 30 d, and refeeding restored the optimum activity levels within the same 30‐d period thereafter.